2020
DOI: 10.1088/1748-0221/15/04/c04025
|View full text |Cite
|
Sign up to set email alerts
|

Method of spatial size measurement of relativistic electrons beams with small bunch length

Abstract: We investigate the practical implementation of a previously proposed method for determining the transverse dimensions of an electron beam on a target by measuring the two-dimensional angular distributions of diffracted transition radiation of relativistic electrons for two distances between the crystal where the radiation is generated and the coordinate detector for femtosecond bunches. We show that determining electron microbunches with small longitudinal sizes requires an increased photon energy, achieved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…When the condition πœ” β‰ͺ π›Ύπœ” p is satisfied, the angular distribution of the intensity of the transition radiation, and hence the DTR, does not depend on the photon energy; therefore, all of the following statements apply to other crystals, observation angles, and reflecting planes. Choosing a different crystal or observation angle will only change the photon energy and reflected radiation yield [29]. The presence of the polarization factor 𝐢 pol in expression (2) leads to a change in the ratio of the intensities of the vertical and horizontal distributions with a change in the observation angle.…”
Section: Description Of Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the condition πœ” β‰ͺ π›Ύπœ” p is satisfied, the angular distribution of the intensity of the transition radiation, and hence the DTR, does not depend on the photon energy; therefore, all of the following statements apply to other crystals, observation angles, and reflecting planes. Choosing a different crystal or observation angle will only change the photon energy and reflected radiation yield [29]. The presence of the polarization factor 𝐢 pol in expression (2) leads to a change in the ratio of the intensities of the vertical and horizontal distributions with a change in the observation angle.…”
Section: Description Of Methodsmentioning
confidence: 99%
“…In all cases, the differences between the estimate and the true value start to exceed the fitting error under the condition 𝜎 β€² π‘₯,𝑦 = 𝜎 π‘₯,𝑦 βˆ•π‘… 2 ≀ 0.1𝛾 βˆ’1 . The reason for this behavior of the fitting results is that the differences between the ''noisy'' distributions π‘Œ 𝑅 1 (πœƒ π‘₯ , πœƒ 𝑦 ) and π‘Œ 𝑅 2 (πœƒ π‘₯ , πœƒ 𝑦 ) decrease with increasing distance between the crystal and the coordinate detector [29], so the method loses its sensitivity. It is also found that with increasing ''noise'' level, the deviation of Οƒπ‘₯,𝑦 from 𝜎 π‘₯,𝑦 begins to manifest itself for smaller distances, and vice versa: with decreasing ''noise'' level, the fitting error decreases, and the deviation of Οƒπ‘₯,𝑦 from 𝜎 π‘₯,𝑦 starts at larger distances.…”
Section: Determination Of the Beam Profile Parametersmentioning
confidence: 99%
“…In this case, DTR can be used instead of PXR, and the measurable beam size is limited by the pixel size of the detector and comparable to 10-15 ΞΌm [19]. Following the work [18,19], we discussed the scheme for determining beam sizes for XFEL linear accelerators [21], and the scheme for determining emittances of 5-10 GeV electron beams [22].…”
Section: Introductionmentioning
confidence: 99%